Biofortified biscuits with indigenous plants: An innovative approach to prevent stunting in early childhood - Akhsanitaqwim, Yochidamai; Arista, Nor Isnaeni Dwi; Septiyanto, Arifin (Public Health Risk Assesment Journal, 2024)
Background: The increase in human living standards is in line with the demands of public health quality. Stunting in Indonesia has reached 37.2%, placing it in fifth place in the world and becoming one of the five major health problems being addressed by the government. This study aims to find the right biscuit formulation from cassava leaves and cowpea seeds as an effort to prevent stunting. Methods: Making biscuits needs to be preceded by making cassava leaf paste and winged bean seed flour and then determining various formulations. Variations in winged bean seed flour formulation: cassava leaf paste, namely F1 (20:10), F2 (25:15), F3 (30:10). Biscuits are made using the cream method, namely mixing sugar, skim milk, margarine and egg yolks until homogeneous then adding wheat flour, winged bean seed flour, cassava leaf paste, water and leavening agent. The dough is rolled, molded and baked at 170 o C for 30 minutes. Findings: after carrying out organoleptic tests to measure product quality and determine the best formulation, it turned out that F2 was the biscuit formulation that the panelists liked most. Conclusion: The development of stunting prevention biscuits from cassava leaves and winged bean seeds is a potential solution. The next step is to disseminate this product as part of a stunting prevention strategy in the community. Novelty/Originality of this Study: The use of local agricultural resources, specifically winged bean seeds and cassava leaves, to develop a nutritious and affordable biscuit aimed at preventing stunting is an innovative approach that not only addresses the chronic malnutrition problem but also supports local economies by utilizing underutilized crops.